Analisis Kadar Merkuri (Hg) Pada Rambut Pekerja Tambang Di Pertambangan Emas Tanpa Izin (PETI) Di Kabupaten Kuansing - Karolina Rosmiati; Dina Silvia (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
Mercury is a harmful and toxic heavy metal in the form of silver-white odorless liquid which is slightly volatile at room temperature. It is commonly used by communities in illegal mining to obtain gold. Amalgamation processes were conducted by adding small quantities of mercury to ores which consequently generate amalgam. Amalgam is subsequently extracted through a smelting process to obtain gold. Skin contact and accidental inhalation can lead to mercury exposure. Hair is one of the biomarkers indicating mercury exposure. The purpose of this study was to analyze the mercury (Hg) levels in illegal gold mining workers’ hair in Kuansing District. A purposive sampling technique was applied with the inclusion criteria were ? 30 years old male, ? 5 years of work period and ? 7 hours work duration in a day, never applied hair dye, and were willing to be the samples. 10 samples of mining workers’ hair were initially prepared with a wet digestion method using HNO3 and HCl. Concentration of mercury was analyzed with Atomic Absorption Spectrophotometer (AAS) at a wavelength of 253.7 nm. The absorbance measurement of standard series solution obtained a linear equation y = 217.481x + 17.121 with correlation coefficient of 0.999. Analysis of mercury levels in 10 hair samples indicated the highest level obtained was 0.0312 ppm, in sample code C and the lowest level was 0,00008 ppm. The permissible limit of mercury exposure in human hair regulated by WHO is 1-2 ppm, thus the mercury levels found were not above the threshold